Self-medication Among Myofascial Pain Patients: A Preliminary Study - Pastore, Gabriel Pires; Goulart, Douglas Rangel; Pastore, Patrícia Radaic; Prati, Alexandre Javaroni; de Moraes, Márcio (The open dentistry journal, 2018)
Self-medication has been reported as an option which people choose to relieve the suffering of conditions that cause pain, however, this could delay the correct diagnosis and therapy. The aim of the present study was to determine the prevalence of self-medication among patients with Temporomandibular Disorder (TMD), and to analyze correlations with the severity of the disease. A prospective study was conducted with patients who had been diagnosed with TMD. The patients were submitted to anamnesis and a physical examination. This research also used the Fonseca`s Anamnestic Index (FAI) and a questionnaire that was developed specifically for this study, containing questions related to the first health professional contacted and self-medication. The data were analyzed using comparative and correlative analysis (Version 18.0 of SPSS software), with the level of significance set at <0.05. Thirty-four patients were included, with a prevalence of females (91.2%) and a mean age of 39.76 years. Half of the patients claimed to have chosen their own medications at time, especially analgesics. Sodium dipyrone was used by 12 of the participants. Dentists were the most commonly contacted health professionals (55.5%). No correlation was found between self-medication and the severity of TMD according to the FAI. Furthermore, the time period between the onset of symptoms and the first consultation was not affected by self-medication. Self-medication seems to be highly prevalent among patients with TMD, although this practice does not seem to alter the severity of the disease.